2017
DOI: 10.1371/journal.pone.0187650
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm monoculture induces drastic erosion of an Amazonian forest mammal fauna

Abstract: Oil palm monoculture comprises one of the most financially attractive land-use options in tropical forests, but cropland suitability overlaps the distribution of many highly threatened vertebrate species. We investigated how forest mammals respond to a landscape mosaic, including mature oil palm plantations and primary forest patches in Eastern Amazonia. Using both line-transect censuses (LTC) and camera-trapping (CT), we quantified the general patterns of mammal community structure and attempted to identify b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 47 publications
10
51
4
3
Order By: Relevance
“…In Brazil there was also very little overlap in the structure of the mammal communities between oil palm plantations and native forest, but this was in part due to the presence of arboreal species in the forest, which we were unable to census in this study (Mendes-Oliveira et al, 2017). Further, in the Brazilian study, 87% of all mammals found in oil palm were never farther than 1.3 km from the forest edge (Mendes-Oliveira et al, 2017). Given that the oil palm plantations in our study were <100 ha, we probably observed some mammal species using the plantations that would not be found in the core of larger plantations.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…In Brazil there was also very little overlap in the structure of the mammal communities between oil palm plantations and native forest, but this was in part due to the presence of arboreal species in the forest, which we were unable to census in this study (Mendes-Oliveira et al, 2017). Further, in the Brazilian study, 87% of all mammals found in oil palm were never farther than 1.3 km from the forest edge (Mendes-Oliveira et al, 2017). Given that the oil palm plantations in our study were <100 ha, we probably observed some mammal species using the plantations that would not be found in the core of larger plantations.…”
Section: Discussionmentioning
confidence: 87%
“…Our results differ somewhat from other studies of oil palm impacts on mammal communities in Latin America, mostly likely due to the differences in plantation sizes. In both Colombia and Brazil, where oil palm plantations are large (>100 ha), species richness and composition of mammals was significantly reduced in oil palm plantations compared to native forests (Mendes-Oliveira et al, 2017;Pardo et al, 2018a). In terms of mammal community structure, in Colombia the riparian fragments had species compositions that were more similar to one another than the oil palm plantations, and there was little overlap in the structure of the two communities (Pardo et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations